Can't stop believing - Thomas, Jodi (Thomas, Jodi. Harmony novel., 2013)
When Nevada Britain agrees to give ex-convict Cord McDowell a piece of land that their families have been fighting over for a hundred years if he will marry her, neither of them expects to fall in love.